Evaluation of VCAM-1 Targeted Naringenin/Indocyanine Green-Loaded Lipid Nanoemulsions as Theranostic Nanoplatforms in Inflammation - Elena Valeria Fuior; Cristina Ana Mocanu; Mariana Deleanu; Geanina Voicu; Maria Anghelache; Daniela Rebleanu; Maya Simionescu; Manuela Calin (MDPI AG, 2020)
Naringenin, an anti-inflammatory citrus flavonoid, is restrained from large-scale use by its reduced water solubility and bioavailability. To overcome these limitations, naringenin was loaded into lipid nanoemulsions directed towards vascular cell adhesion molecule (VCAM)-1, exposed by activated endothelium, and delivered intravenously in a murine model of lipopolysaccharide (LPS)-induced inflammation. To follow the in vivo bio-distribution, naringenin-loaded nanoemulsions were labeled with near-infrared probe Indocyanine Green (ICG). Based on ICG fluorescence, a VCAM-1-dependent retention of nanoemulsions was detected in the heart and aorta, while ultra-high-performance liquid chromatography (UHPLC) measurements showed a target-selective accumulation of naringenin in the heart and lungs. Correlated, fluorescence and UHPLC data indicated a mixed behavior of the VCAM-1 directed nanoparticles, which were driven not only by the targeting moiety but also by passive retention. The treatment with naringenin-loaded nanoemulsions reduced the mRNA levels of some inflammatory mediators in organs harvested from mice with acute inflammation, indicative of their anti-inflammatory potential. The data support a novel theranostic nanoplatform for inflammation, the naringenin/ICG-loaded nanoparticles that either by passive accumulation or effective targeting of the activated endothelium can be employed for imaging inflamed vascular areas and efficient delivery of the encapsulated therapeutic agent.